SOUTH KOREAN STUDENTS' PERSPECTIVES ON THE NEED FOR BIPA READING TEACHING MATERIALS BASED ON LIVELIHOOD CULTURE - Dinar Asri; Suci Sundusiah; Mochamad Whilky Rizkyanfi (RADJA PUBLIKA, 2025)
This study aims to identify the views of South Korean students on Indonesian Language reading materials for Foreign Speakers (BIPA) that raise the theme of livelihood culture. The method used is descriptive qualitative with data collection techniques through questionnaires filled out by Busan University of Foreign Studies BIPA 3 and 4 students. The results of the study show that students are interested in cultural themes, such as civet coffee, salt farmers in Bali, and Minang restaurants. They expect reading materials that are presented digitally and interactively, equipped with supporting images or videos to be more interesting and easy to understand. In addition, students consider the similarity of cultural values ​​between Indonesia and South Korea as a factor that facilitates understanding and increases interest in learning.